Case Report On Ayurvedic Management of Hair Fall - Sason, Rajveer; Sharma, Monika (International Research Journal of Ayurveda & Yoga, 2021)
Hair plays a vital role in the personality of human and for their care we use lots of cosmetic products. The fading (pigmentation problem), dandruff, alopecia (loss of hair) is the major problem associated with hairs. It is said that face is the mirror of our personality and it should be maintained from the hairstyle we keep. In today’s developing world there are lots changes in the eating habits and the lifestyle. This is a case report of 28 years female with complaint of Hair loss for 1 year. Patient was treated with ayurvedic preparations for 2 months. Decrease in hair fall was achieved successfully. Patient felt relieved of itching and redness of scalp also. This case study reveals the potential of Ayurvedic management of Hair fall.